Prevalence of HIV and syphilis infection among high school and college student MSM in China: a systematic review and meta-analysis. - Yongze Li; Junjie Xu; Kathleen H Reilly; Jianming Zhang; Hongyi Wei; Yongjun Jiang; Wenqing Geng; Weiming Tang; Hong Shang (PLoS ONE)
Objectives The aim of this study is to systematically review the published studies and summarize the estimates of HIV and syphilis prevalences among high school and college student MSM in China in order to provide information for conducting targeted interventions. Methods Pubmed, Chinese National Knowledge Infrastructure, Wanfang and Google Scholar databases were searched in January 2013 to identify relevant articles. Data of eligible citations were extracted by two reviewers. All analyses were performed using Comprehensive Meta-Analysis V2.0 and SPSS V17.0. Results Twenty-four eligible studies (6 in English and 18 in Chinese), published between 2006 and 2012, with a total of 3083 student MSM participants, were included. The meta-analyses showed that the prevalences of HIV and syphilis among studied student MSM were 4.4% (95% CI: 3.0%, 6.4%) and 5.7% (95% CI: 4.8%, 6.7%), respectively. HIV prevalence increased over the study period (3.0% in 2003-2006; 4.5% in 2007-2008, and 6.8% in 2009-2010, trend test chi-square =11.3, p = 0.001). Conclusions Student MSM have become high-risk populations for HIV infection in China. The high prevalence of syphilis and the increasing HIV prevalence trend indicate the potential for a more severe HIV epidemic. Comprehensive intervention strategies that address condom promotion, syphilis detection and treatment, and health education need to be tailored to this vulnerable population to prevent HIV and syphilis infections.